Developing novel blood‐based biomarkers for Alzheimer's disease. Issue 1 (1st January 2014) - Snyder, Heather M.; Carrillo, Maria C.; Grodstein, Francine; Henriksen, Kim; Jeromin, Andreas; Lovestone, Simon; Mielke, Michelle M.; O'Bryant, Sid; Sarasa, Manual; Sj⊘gren, Magnus; Soares, Holly; Teeling, Jessica; et al.
Abstract: Alzheimer's disease is the public health crisis of the 21st century. There is a clear need for a widely available, inexpensive and reliable method to diagnosis Alzheimer's disease in the earliest stages, track disease progression, and accelerate clinical development of new therapeutics. One avenue of research being explored is blood based biomarkers. In April 2012, the Alzheimer's Association and the Alzheimer's Drug Discovery Foundation convened top scientists from around the world to discuss the state of blood based biomarker development. This manuscript summarizes the meeting and the resultant discussion, including potential next steps to move this area of research forward.